Effect of Wuzi Yanzong prescription on oligoasthenozoospermia rats based on UPLC-Q-TOF-MS metabolomics. (31st December 2022) - Chen, Zhimin; Dong, Baohua; Jiang, Yunxiu; Peng, Ying; Li, Wenbing; Yu, Lingying; Gao, Yongxiang; Hu, Changjiang
Abstract: Context: Wuzi Yanzong Prescription (WYP) has long been used to treat male infertility, with convincing clinical evidence. However, its mechanism of action is not clear. Objective: WYP chemical components were quantified by HPLC, and the effect on oligoasthenozoospermia rats was explored based on UPLC-Q-TOF-MS metabonomics technology. Materials and methods: The solution was extracted by alcohol and water; the content of eight components in the extracting solution was determined by HPLC. Twenty-four Sprague-Dawley rats were randomly divided into control (CG), model (MG) and administration (PG) groups. Oligoasthenozoospermia was induced for 30 days in all, but the CG with daily oral doses of 20 mg/kg Tripterysium glycosides (TG). PG was given daily oral doses of WYP solution (1.08 g/kg), CG and MG received the same volume of distilled water, all administered for 30 days. After the last administration, the serum samples were collected and detected by UPLC-Q-TOF-MS. Results: An HPLC method for simultaneous determination of chlorogenic acid (0.081%), ellagic acid (0.021%), hyperoside (0.032%), verbascoside (0.011%), isoquercitrin (0.041%), astragalin (0.026%), kaempferol (0.009%) and schisandrin (0.014%) was established. Moreover, the 74 potential biomarkers and eight metabolic pathways related to oligoasthenozoospermia were identified by multivariate analysis and metabolite profiling. WYP can regulate 36 markers, mainly involving amino acid metabolism, lipid metabolism and nucleotide metabolism. Discussion and conclusions: This is a simple and accurate method for quality control of WYP. It further enriches the potential mechanism of WYP in the treatment of oligoasthenozoospermia. It can provide a theoretical basis for the rational application of WYP.